7 practices of effective ministry - Stanley, Andy.; Joiner, Reggie; Jones, Lane. (Sisters, Or. : Multnomah Publishers, 2004)
Like your own personal trainer, 7 Practices of Effective Ministry is an insightful guide for any leader who yearns for a simpler, more effective approach to ministry. Here are seven strategic principles that when put into play will bring focus and clarity to everything you do and turn your ministry into a winning team.
Preface: A new season -- The best-laid plans -- Throwing strikes -- Keeping score -- Getting on base -- Staying focused -- Teaching the fundamentals -- The roar of the crowd -- Developing new talent -- Managing your way to victory -- Practice #1: Clarify the win -- Practice #2: Think steps, not programs -- Practice #3: Narrow the focus -- Practice #4: Teach less for more -- Practice #5: Listen to outsiders -- Practice #6: Replace yourself -- Practice #7: Work on it -- Epilogue: A final challenge.
Includes bibliographical references (p. 187).
Keywords: Pastoral theology